Morphological analysis of karst features based on very high-density point clouds - Konsolaki, A.; Vassilakis, Emm.; Giannopoulos, V. (Reg. Conf. on Geomorphology (IAG), 2019)
The generation of rock cavities and especially of those created under karstic procedures is a matter of research for the last decades. A high-resolution subsurface morphology could be produced after scanning the entire cave with state-of-the-art equipment based on Light Detection And Range technology. A handheld laser scanner was used for acquiring points with projected coordinate information (X,Y,Z) covering the entire show cave of Koutouki (Athens, Greece), including its hidden passages and dark corners. The point cloud covers the floor, the walls and the roof of the cave, as well as the stalactites, stalagmites and the connected columns that constitute the decoration of the cave. The absolute and exact placement of the point cloud within a geographic reference frame gives us the opportunity for three-dimensional measurements and detailed visualization of the subsurface structures.